The Oxygen Saturation in the Retinal Vessels of Patients with Diabetes Mellitus – The Search for Determinants - Stodtmeister, Richard; Mielke, Vivien; Sandner, Dirk (Klinische Monatsblätter für Augenheilkunde, 2021)
Introduction Oxygen saturation in retinal vessels can be non-invasively measured by a new method. It is known that oxygen extraction is lowered in diabetic retinopathy. In the cross-sectional study presented here, it has been investigated whether diabetes-specific changes and typical accompanying diseases could influence the measurements in oximetry.Methods During a time span of seven months, 237 diabetics were included who came to our clinic for an intravitreal injection, who met the inclusion criteria, who showed no exclusion criteria and gave written consent. 203 eyes of 203 patients were evaluated. The oxygen saturation (SO2) was measured in digitally stored fundus images taken with a fundus camera (Zeiss 450 FF). In its illumination beam, a filter was inserted with two transmission maxima at 584 nm and 610 nm (bandwidth 10 nm). With the program “Oximetry” (Imedos Systems, Jena, Germany), the venous and the arterial SO2 were measured. The values were stored in a spreadsheet. Diabetes related data, clinical parameters and accompanying diseases were documented in the predefined scheme.Results In the whole patient sample, the venous oxygen saturation (vSO2) was 69 ± 12%, the arterial saturation (aSO2) 99 ± 5% and the arteriovenous difference 31 ± 9%. A statistically significant association could not be found between the measurement values of oximetry and age, duration of diabetes and HbA1c (Kruskal-Wallis ANOVA: p > 0.05). The differences in oximetry values between units of analysis (UOA) e.g. hypertension and non units of analysis (NOA) were analysed. Descriptive testing showed significant differences in vSO2% in the following units of analysis: allergies n = 47: UOA vs. NUOA: 64 vs. 69 (t test: p < 0.02); sartan therapy n = 46: UOA vs. NUOA: 64 vs. 70 (p = 0.003); state after intravitreal injections n = 144: 68 vs. 71 (p = 0.02). Oxygen extraction from the retinal capillaries was improved in patients who had injections with VEGF inhibitors. An improvement in oxygen extraction is also seen in patients with allergies and hypertension in comparison to those without these units of analysis.Conclusion The clinically observed improvement in the retinal state situation after intravitreal injections with VEGF inhibitors may be seen in association with the improved oxygen extraction. It seems reasonable to study whether a switch to sartans in the therapy of hypertension may improve retinal function.Einleitung Mit der neuen Methode der Oximetrie kann nicht invasiv die Sauerstoffsättigung (SO2) in den retinalen Gefäßen gemessen werden. Es ist bekannt, dass bei der diabetischen Retinopathie die Sauerstoffextraktion verringert ist. In der vorgelegten Querschnittsstudie wurde untersucht, ob diabetesspezifische Veränderungen und typische Begleiterkrankungen die Messwerte bei der Oximetrie verändern können.Methodik 237 Diabetespatienten wurden eingeschlossen, die zu einer Behandlung mit intravitrealen Injektionen (IVOM) in unsere Klinik kamen. Ausgewertet werden konnten 203 Augen von 203 Patienten. Die SO2 in den retinalen Gefäßen wurde gemessen an digital gespeicherten Aufnahmen einer Funduskamera (Zeiss 450 FF), deren Beleuchtungsstrahlengang mit einem Filter mit 2 Durchlassmaxima bei 548 nm und bei 610 nm (Bandbreite 10 nm) versehen war. Mit dem Programm „Oximetrie“ (Imedos Systems, Jena) wurden die arterielle und die venöse Sauerstoffsättigung in Arteriolen und Venolen gemessen und in einer Excel-Tabelle ausgegeben. Diabetesbezogene anamnestische Daten, klinische Parameter und Begleiterkrankungen wurden in einem festgelegten Schema dokumentiert.Ergebnisse Im gesamten Patientenkollektiv war die venöse Sauerstoffsättigung (vSO2) 69 ± 12%, die arterielle Sauerstoffsättigung (aSO2) 99 ± 5% und die arteriovenöse Differenz 31 ± 9%. Ein statistisch signifikanter Zusammenhang zwischen Alter, Diabetesdauer und HbA1c mit den Oximetriewerten konnte nicht gefunden werden (Kruskal-Wallis ANOVA: p > 0,05). Untersucht wurden die Differenzen zwischen den Merkmalsträgern (MT) und Nichtmerkmalsträgern (NMT). Hier zeigten sich signifikante Unterschiede der vSO2 in % für: Allergien n = 47: MT vs. NMT: 64 vs. 69 (t-Test: p < 0,002); Sartan-Therapie n = 46: MT vs. NMT: 64 vs. 70 (p = 0,003). Zustand nach IVOM n = 144: MT vs. NMT: 68 vs. 71 (p = 0,02). Bei Patienten mit durchgeführten IVOM im Rahmen einer diabetischen Makulopathie verbessert sich somit die Sauerstoffextraktion aus den Netzhautgefäßen. Bei Allergikern und bei Hypertoniepatienten unter einer Sartan-Therapie konnte dies ebenfalls gezeigt werden.Schlussfolgerung Die klinisch beobachtete Besserung der Netzhautsituation nach intravitrealen Injektionen mit VEGF-Hemmern kann im Zusammenhang stehen mit einer verbesserten Sauerstoffextraktion aus den Netzhautgefäßen. Es erscheint sinnvoll zu prüfen, ob bei Diabetespatienten in der Hypertoniebehandlung die Umstellung auf Sartane die Netzhautfunktion verbessern kann.
Keywords: retina; diabetes mellitus; oximetry; sartans; VEGF inhibitors; allergy